Factors Influencing Investment Decisions among College Students: A Comparative Analysis Between India & Nigeria - Devanshu Karamchandani; Anjali Anjali; Etoo Emmanuel Obinwa; R Devi Nandana; Kunal Panda; Gan Kia Hui; Okwu Peter; Rudresh Pandey; Teoh Bak Aun; Lok Yee Huei (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
Investment is done for the purpose to gain profitable returns. Investing in a well-diversified portfolio offers a multitude of benefits, including capital appreciation to grow wealth over time. As a student, managing finance can be challenging, but exploring opportunities for passive income can make a significant difference in financial stability and independence. This study endeavors to comparatively analyze the factors influencing investment decisions among college students in India and Nigeria. Demographics play a pivotal role in shaping investment choices, and understanding the differences in the attitude of these countries is vital for effective financial education initiatives. The study reveals that there is a positive relationship between different factors that students consider when making these decisions. Factors such as financial security, return on investment (ROI), and risk minimization are found to have a significant impact on their choices.